Knowledge and Perceptions of Cypriots about Oral Cancer - Charalambous Chrystala; Pantelas Georgios; Nikolentzos Athanasios; Theodorou Mamas (Balkan Stomatological Society, 2014)
Introduction: Oral cancer is the sixth most common cancer in the world. Cyprus recorded 312 new cases between 1998 and 2009, which represent a significant percentage of all cancers reported in Cyprus.